Examining the Relationships Among Perceived Quality, Perceived Value, Customer Satisfaction, and Behavioral Intention in Turkish Fitness Centers - Sevilmiş Ali; Özdemir İlknur; García-Fernández Jerónimo; Zhang James Jianhui (Sciendo, 2022)
The purpose of this study is to analyze the relationships among perceived quality, perceived value, customer satisfaction, and behavioral intention in Turkish fitness centers. The data were collected from 305 fitness customers (149 women and 156 men) using the quantitative method of a questionnaire. The main procedure of this study was to conceptualize fitness clubs' perceived value as a multidimensional construct of four dimensions. Through a comprehensive review of the literature, a questionnaire was developed to measure perceived quality, perceived value, customer satisfaction, and behavioural intention, which took into consideration the unique characteristics of Turkish fitness centers. After examining the measurement properties by conducting confirmatory factor analysis and structural equation model analysis, the results revealed positive relationships among perceived quality, perceived value, customer satisfaction, and behavioral intention. The findings showed that perceived quality was positively related to social value, functional value, emotional value, and economic value. Likewise, functional value and economic value were positively related to customer satisfaction, and social value and emotional value were not positively related to customer satisfaction. Finally, customer satisfaction was related to behavioral intentions. The implication for management is significant as it shows that quality management is important for the different dimensions of value. Therefore, sports managers must work on quality processes to achieve positive perceived quality and its consequences, such as perceived value or behavioral intentions. This chain of positive perceptions improves consumer loyalty.